Semantic Properties of Pronouns Modulate Pronoun Use: Evidence from Cantonese. Issue 1 (2nd January 2018) - Hwang, Heeju
Abstract : Pronouns vary across languages in terms of their specification of semantic features. For example, the third singular pronoun in Cantonese ( keoi ), unlike in English, does not make distinctions of gender and animacy. The present study aims to provide insight into how semantic properties of pronouns modulate speakers' choice of referring expression by investigating pronoun use in a language with different feature specifications from English, namely Cantonese. Using a story completion task, we found that unlike in English, the gender of discourse entities did not influence pronoun use in Cantonese (Experiment 1). In contrast to gender, we found that animacy had a significant influence on Cantonese speakers' pronoun use (Experiment 2). We suggest that semantic features such as animacy that are inherently linked to the accessibility of a referent may influence pronoun use irrespective of semantic properties of pronouns, whereas features such as gender that are not inherently linked to referent accessibility may only influence reference production via interaction with pronouns.